1997
DOI: 10.1091/mbc.8.7.1261
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 6 functions in trans-Golgi network vesicle trafficking.

Abstract: The specific transfer of vesicles between organelles is critical in generating and maintaining the organization of membrane compartments within cells. Syntaxin 6 is a recently discovered member of the syntaxin family, whose constituents are required components of several vesicle trafficking pathways. To better understand the function of syntaxin 6, we generated a panel of monoclonal antibodies that specifically recognize different epitopes of the protein. Immunoelectron microscopy shows syntaxin 6 primarily on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
240
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(259 citation statements)
references
References 46 publications
17
240
0
2
Order By: Relevance
“…The Golgi apparatus is involved in vesicular traffic. A number of SNARE proteins, such as yeast Sed5p (Banfield et al, 1994) and mVps45 (Tellam et al, 1997), mammalian syntaxin 6 (Bock et al, 1997), VAMP4, Syntaxin 13, and mVtib (Advani et al, 1998), have all been reported to be localized to the Golgi. Rat munc13-1 has been shown to interact with a number of proteins involved in vesicle docking and trafficking, such as syntaxin (Betz et al, 1997) and Doc2 (Orita et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi apparatus is involved in vesicular traffic. A number of SNARE proteins, such as yeast Sed5p (Banfield et al, 1994) and mVps45 (Tellam et al, 1997), mammalian syntaxin 6 (Bock et al, 1997), VAMP4, Syntaxin 13, and mVtib (Advani et al, 1998), have all been reported to be localized to the Golgi. Rat munc13-1 has been shown to interact with a number of proteins involved in vesicle docking and trafficking, such as syntaxin (Betz et al, 1997) and Doc2 (Orita et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Syntaxin 6 is a trans-Golgi network protein and regulates membrane trafficking (36). Partial colocalization of CDCP1-containing vesicles with syntaxin Fig.…”
Section: Cdcp1 Localizes To Lipid Raft-containing Vesicular Structurementioning
confidence: 99%
“…Rabbit antisera for sec22b (Hay et al, 1998), VAMP2 (Pevsner et al, 1994), and VAMP4 (Steegmaier et al, 1999), and mouse mAbs for rbet1 (Hay et al, 1998), syntaxin 1 (Inoue et al, 1992), syntaxin 6 (Bock et al, 1997), and syntaxin 13 (Prekeris et al, 1998), have been described previously. Antibodies for calnexin, cytochrome C, human LAMP1, and myc (clone 9E10) were purchased from Stressgen (Victoria, British Columbia, Canada), PharMingen (San Diego, CA), Transduction Laboratories (Lexington, KY), and Santa Cruz Biotechnology (Santa Cruz, CA), respectively.…”
Section: Antibodiesmentioning
confidence: 99%